1998
DOI: 10.1046/j.1460-9568.1998.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of ornithine decarboxylase activation in transient focal cerebral ischaemia: a study using ornithine decarboxylase-overexpressing transgenic rats

Abstract: Nuclear magnetic resonance imaging (MRI) was used to study dynamics of maturation and the size of ischaemic stroke lesions in rats with greatly increased activity of ornithine decarboxylase (ODC). Syngenic rats, either with or without chronic pre-ischaemic treatment with an ODC inhibitor, alpha-difluoromethylornithine (DFMO), as well as ODC-overexpressing transgenic rats were subjected either to transient middle cerebral artery (MCA) occlusion or permanent occlusion of the cortical branch of MCA. The two model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…On the other hand, ODC activation and putrescine accumulation showed either no effect or neuroprotection in transient focal cerebral ischemia (Keinanen et al, 1997;Lukkarinen et al, 1997Lukkarinen et al, , 1998. Previous work from our laboratory has shown induction of ODC and subsequent alterations in polyamine metabolism, particularly an increase in putrescine levels, to be an important factor in bloodbrain barrier dysfunction and the development of vasogenic edema after CNS injury (Dempsey et al, 1991;Kindy et al, 1994;Rao et al, 1995Rao et al, , 1997Başkaya et al, 1997b,c).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, ODC activation and putrescine accumulation showed either no effect or neuroprotection in transient focal cerebral ischemia (Keinanen et al, 1997;Lukkarinen et al, 1997Lukkarinen et al, , 1998. Previous work from our laboratory has shown induction of ODC and subsequent alterations in polyamine metabolism, particularly an increase in putrescine levels, to be an important factor in bloodbrain barrier dysfunction and the development of vasogenic edema after CNS injury (Dempsey et al, 1991;Kindy et al, 1994;Rao et al, 1995Rao et al, , 1997Başkaya et al, 1997b,c).…”
mentioning
confidence: 92%
“…Previous work from our laboratory has shown induction of ODC and subsequent alterations in polyamine metabolism, particularly an increase in putrescine levels, to be an important factor in bloodbrain barrier dysfunction and the development of vasogenic edema after CNS injury (Dempsey et al, 1991;Kindy et al, 1994;Rao et al, 1995Rao et al, , 1997Başkaya et al, 1997b,c). Inhibition of ODC by ␣-difluoromethylornithine either protected the brain from ischemic damage (Schmitz et al, 1993;Kindy et al, 1994) or enhanced the infarct volume in focal cerebral ischemia (Lukkarinen et al, 1998).…”
mentioning
confidence: 99%
“…A hyperacute lesion seen with DWI does not necessarily indicate infarction, because early cellular changes of ischemia (eg, cytotoxic edema) may potentially be reversed and lesion growth may be attenuated by reperfusion or neuroprotective drugs. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Human studies of stroke with DWI and perfusion MRI have confirmed the ability of these methodologies to detect early ischemic lesions. 40 -47 Correlations of initial lesion volume by DWI to final infarct size on T2-weighted MRI have been observed, as have correlations of acute lesion volumes by DWI and chronic lesion volumes by T2-weighted imaging to scores of stroke clinical severity scales.…”
mentioning
confidence: 99%
“…Polyamine biosynthesis is regulated by the activities of ornithine and S-adenosylmethionine decarboxylases. Overexpression of ornithine decarboxylase in transgenic rodents affected spermatogenesis (1,2), rendered animals more resistant to chemically or electrically induced seizure activity (3) and to ischemic insults (4), and enhanced skin papilloma formation (5). However, the activation of polyamine biosynthesis caused by overexpression of ornithine decarboxylase did not result in enhanced accumulation of the higher polyamines spermidine and spermine.…”
mentioning
confidence: 99%